A case report of breast Rosai-Dorfman disease and a literature review - Lin, Yuan; Wang, Ya-Wen; Li, Li-Xin; Qiao, Zhong-Qi; Chen, Xu; Chen, Yan-Duo; Liu, Can; Zhang, Kai (Frontiers in Oncology, 2025)
Rosai-Dorfman disease (RDD) is a rare idiopathic histiocytoproliferative disease that usually affects the lymph nodes of the head and neck, but can also involve extranodal sites such as the skin, sinuses, and soft tissues. Breast RDD is exceedingly rare. It may be clinically and radiographically similar to neoplastic and non-neoplastic diseases. We report a case of breast RDD in a 68-year-old female patient and describe the clinical imaging and pathological features of the patient. The management of extranodal RDD is individualized, and there are no standardized guidelines for treatment. We highlight the importance of considering the diagnosis of extranodal breast RDD, and suggest that surgical resection is an effective way to treat this disease, particularly for single-focal breast lesions with RDD.